2007
DOI: 10.1093/jxb/erm236
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hormones and KNOXI genes in early Arabidopsis seedling development

Abstract: Plant hormones control plant development by modulating the expression of regulatory genes, including homeobox-containing KNOXI genes. However, much remains to be elucidated about the interactions involved. Therefore, hormonal regulation of KNOXI gene expression was investigated using hormone applications and an inducible transgenic ipt expression system to increase endogenous cytokinin (CK) levels. Treatments with auxin, abscisic acid (ABA), cytokinins, ethylene, and gibberellin (GA) did not result in ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…; Souček et al . ) and proteomic responses (Černý et al . ), without causing cytotoxic effects within 15 min of treatment (Mlejnek et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Souček et al . ) and proteomic responses (Černý et al . ), without causing cytotoxic effects within 15 min of treatment (Mlejnek et al .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, high auxin levels down‐regulate the expression of KNOX genes (Shani et al. , 2006), and it has been suggested that KNOX proteins may inhibit the transport of auxin (Soucek et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4a). Interestingly, the KNAT1 homeobox transcription factor is expressed at the base of LR primordia (Truernit et al ., 2006) and is auxin‐induced and ABA‐repressed in LR primordia (Soucek et al ., 2007), suggesting a possible point of integration for the two signals. Further research is needed to establish ABA as an inhibitor of LR initiation in Arabidopsis .…”
mentioning
confidence: 99%